CASA-BASED EVALUATION OF SPERM MOTILITY AT FROZEN-THAWED STAGE IN HARIANA BULLS - KUMAR, U; PATI, P; JENA, B; MOHANTY, DN; MISHRA, PC; PRADHAN, SK; NAHAK, AK (The Indian Journal of Animal Reproduction, 2016)
Thawed frozen semen of Hariana bulls (n=4, one straw from each of 15 ejaculates per bull) was evaluated by CASA for sperm motion and velocity parameters. One of the bulls had higher (p
Keywords: CASA; Fertility; Frozen semen; Hariana bull; Thawing